Abnormal prion protein in the retina of the most commonly occurring subtype of sporadic Creutzfeldt-Jakob disease. Issue 9 (19th August 2005) - Head, M W; Peden, A H; Yull, H M; Ritchie, D L; Bonshek, R E; Tullo, A B; Ironside, J W
Abstract : Background: Involvement of the eye has been reported in patients with variant Creutzfeldt-Jakob disease (vCJD), but there is disagreement on whether retinal involvement occurs in sporadic Creutzfeldt-Jakob disease (sCJD). Methods: Western blotting, paraffin embedded tissue blotting, and immunohistochemistry were used to test whether the abnormal form of the prion protein (PrP Sc ) accumulates to detectable levels in the eye in a case of the most common subtype of sCJD (MM1). Results: Low levels of PrP Sc were detectable in the retina, localised to the plexiform layers of the central retina. PrP Sc was not detectable in other ocular tissues. Conclusions: The abnormal form of the prion protein is present in the retina in the most common sCJD subtype (MM1), albeit at levels lower than those found previously in vCJD and in sCJD of the VV2 subtype.